Injurious Exploitation: The Effects of the Sino-Soviet Summit on the 1989 Tiananmen Square Protests - Lewis, Andrew (Kansas State University. Dept. of History, 2012)
The disruption of the Sino-Soviet Summit was a significant, contributing factor in the violent crackdown in Tiananmen Square on June 4, 1989. The summit was a landmark political event for the People’s Republic of China (PRC), attracting worldwide media attention to Beijing. This presented a unique opportunity to show that China’s brand of socialism was healthy and that the country was ready to solidify its improving relationship with the Soviet Union. Despite the advice of Chinese intellectuals and governmental threats, the students made a conscious decision to exploit, and thereby disrupt, the summit. The demonstration completely overshadowed the summit and created an international perception of the Chinese government that called into doubt its very sovereignty. Government leaders were humiliated on the world stage. This humiliation contributed to the decision to institute martial law, which created an increasingly volatile atmosphere in Beijing. Paranoid of potential protester violence created by martial law, the government ordered troops to clear the Square. In doing so, thousands of Chinese civilians were killed, many of them students, resulting in one of the greatest
Keywords: China; Communism; Summit; Tiananmen; June 4; 1989